2008
DOI: 10.1111/j.1542-4758.2008.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sexual hormone abnormalities on proximal femur bone mineral density in hemodialysis patients and the possible role of RANKL

Abstract: Sexual hormone concentrations are commonly affected in chronic renal failure. The contribution of sex steroids to bone turnover regulation implies that sex steroid's dysfunction may be implicated in the emergence of renal osteodystrophy. This study was conducted to evaluate sex steroids and gonadotrophins in hemodialysis (HD) patients and to investigate their role in bone homeostasis in concert with other hormones and cytokines. Bone mineral density (BMD) at the proximal femur and intact parathyroid hormone (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…It is possible that bone mineral disorders in uremia may override the associations of endogenous testosterone and phosphate observed at a community level. However, testosterone levels have been negatively associated with bone mineral disorders and receptor activator of nuclear factor -B ligand levels in men undergoing hemodialysis (20).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that bone mineral disorders in uremia may override the associations of endogenous testosterone and phosphate observed at a community level. However, testosterone levels have been negatively associated with bone mineral disorders and receptor activator of nuclear factor -B ligand levels in men undergoing hemodialysis (20).…”
Section: Discussionmentioning
confidence: 99%
“…13 Despite the increased prevalence of hypogonadism and its potential consequences, limited data are available on the influence of endogenous testosterone and replacement therapy in CKD patients. 16 However, testosterone abnormalities have recently been linked to disorders in bone composition, 17 to sRANKL levels, 17 and to endothelial dysfunction 18 in CKD patients. In light of the association between low testosterone concentrations and the risk of developing future cardiovascular events recently reported in nonrenal patient groups, 5,19 we evaluated the possible contribution of testosterone levels to the poor prognosis and the elevated CVD risk of male hemodialysis (HD) patients.…”
mentioning
confidence: 99%
“…In the same time the pivot role of estrogens on bone formation recently has also been underlined (Leder et al, 2003;Riggs et al, 2002). The relative contribution of sex steroids on bone health and turnover remains still unclear, particularly in HD patients with HPT, because gonadal hormones concentrations are usually affected in chronic renal failure (Doumouchtsis et al, 2008(Doumouchtsis et al, , 2009. Cytochrome P450 enzyme aromatase system is a key component converting adrenal and testicular C19 steroids into C18 steroids.…”
Section: Introductionmentioning
confidence: 99%
“…(Doumouchtsis et al, 2008;GalMoscovici & Sprague, 2007;Gardham et al, 2010;Hamada & Fukagawa, 2009;Moe et al, 2007). Recent studies of androgens on bone physiology and mineral metabolism at cellular level in animal models and humans revealed that androgen steroids influence bone mass, age related bone loss and the occurrence of fractures, especially in elderly men (Ebeling, 1998(Ebeling, , 2010Lindberg et al, 2005;Vanderschueren et al, 2004) Nevertheless, the specific role of androgens in bone metabolism and skeletal maintenance in men and women is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation